Symptomatic extraforaminal gas-containing pseudocyst treated with unilateral biportal endoscopic spinal surgery: a case report and literature review - Zhang, Ya-wen; Xu, Bin; Wang, Xu-ke; Zheng, Ao-te (Frontiers in Surgery, 2025)
BackgroundGas-containing pseudocyst is an uncommon cause of lumbar radiculopathy and most lumbar gas-containing pseudocysts locate in the spinal canal. While, extraforaminal gas-containing pseudocysts are very rare. Here, we reported a case of extraforaminal gas-containing pseudocyst, which compressed L4 exiting nerve root and caused lumbar radiculopathy.Case presentationA 62-year-old female presented with low back pain and radiation to anteromedial aspect of right thigh and anterior aspect of right calf. Computed tomography and magnetic resonance imaging of lumbar spine showed a gas-containing pseudocyst compressing in L4 exiting nerve root right extraforaminal area at L4–5 level. L4 exiting nerve root blocking was performed to confirm the responsible level. Then we performed BESS through a paraspinal approach to remove the gas-containing pseudocyst and release L4 exiting nerve root. Postoperatively, the patient achieved a good outcome and the pain was relieved.ConclusionsLumbar gas-containing pseudocyst in extraforaminal area is rare and can cause lumbar radiculopathy. Paraspinal approach BESS is an alternative method to treat extraforaminal gas-containing pseudocyst and can provide good outcome.